Energy consumption modelling and benchmarking in continuous galvanising lines. (10th May 2010) - Gopalakrishnan, Bhaskaran; Chavan, Raviraj Ratnakar; Gupta, Deepak; Alkadi, Nasr E.
The pot hardware in continuous galvanising lines is prone to failure and needs to be replaced quite frequently which results in considerable loss of production time and high energy consumption. Galvanizing Energy Profiler and Decision Support Systems (GEPDSS) was developed to consider major energy consuming equipment in a typical hot dip continuous line which tracks the current production and energy consumption for up to three different processes. It can simulate a scenario to identify energy, cost, and productivity benefits obtained from energy savings measures and can evaluate the economic desirability of investment in new and improved pot hardware.